Application and Analysis of a Salt Bridge Reference Electrode Setup for PEM Water Electrolysis: Towards an Extended Voltage Loss Break Down. Issue 12 (1st December 2022) - Bühre, Lena V.; Bullerdiek, Sven; Trinke, Patrick; Bensmann, Boris; Deutsch, Anna-Lena E. R.; Behrens, Peter; Hanke-Rauschenbach, Richard
Abstract : Information on PEMWE performance is often obtained from full cell measurements. The level of detail of this information is, however, comparably low. This contribution analyzes kinetic parameters for anode and cathode reactions separately as a step towards an extended loss breakdown through a salt bridge reference electrode. The reference electrode setup is shown in detail, and qualitative measurements are discussed. OER and HER Tafel slopes and exchange current densities for both reactions are reported. An outlook on future use cases for the salt bridge reference electrode is given and supported by measurement data.